An Event Study of Simultaneous Earthward and Tailward Reconnection Exhaust Flows in the Earth's Midtail. Issue 6 (3rd June 2020) - Wang, Chih‐Ping; Liu, Yi‐Hsin; Xing, Xiaoyan; Runov, Andrei; Artemyev, Anton; Zhang, Xiaojia
Abstract: We report an event of two‐satellite measurements of simultaneous earthward and tailward fast flows of 500 km/s in the midtail at X −63 RE and evaluate magnetic reconnection as a responsible mechanism by comparing the observations with a particle‐in‐cell (PIC) simulation. The two satellites were near midnight separated mainly along the X direction by 5 RE . As they moved across the current sheet from the northern to southern lobes, the one closer to the Earth crossed the x line with fast flows changing from tailward to earthward, while the other one simultaneously observed tailward flows. The observed plasma and fields showed several key reconnection signatures, including the Walén relation, the fast reconnection rate of 0.1, the Hall magnetic and electric fields, and counterstreaming electrons in the separatrix, indicating the fast flow was the reconnection exhaust. The observed temporal variations of flow speeds and magnetic fields suggested that the x line was moving tailward to a location between the two satellites and the exhaust was moving up and down. Within the exhaust, plasma pressure was highly anisotropic, and the current sheet can be unstable to the mirror, ion cyclotron, and firehose instabilities. Current sheet flapping and enhanced compressional waves near proton's local gyro frequencies were observed around the current sheet. Comparing with the PIC simulation suggests that the waves were mainly a result of oblique firehose instability. Key Points: Earthward and tailward fast flows were observed simultaneously by two ARTEMIS probes in midtail The characteristics of the fast flows are consistent with the reconnection exhaust Enhanced compressional ULF waves observed within the fast flow were likely a result of oblique firehose instability